A Permian methane seep system as a paleoenvironmental analogue for the pre-metazoan carbonate platforms - Warren, Lucas Verissimo [UNESP]; Quaglio, Fernanda; Simoes, Marcello Guimaraes [UNESP]; Assine, Mario Luis [UNESP]; Alessandretti, Luciano; Luvizotto, George Luiz [UNESP]; Riccomini, Claudio; Strikis, Nicolas Misailidis (Soc Brasileira Geologia, 2017)
Following the rise of metazoans, the beginning of bioclasticity and substrate competition, the saga of microbial mats was in a fluctuating decline in the end of the Neoproterozoic era. Increases in diversity during the Phanerozoic and punctual upturns in the microbial carbonate production occured after the events of global mass extinctions. Gradually along the Phanerozoic, the microbial colonies occupied isolated niches and grazers-free environments, characterized by physically and/or geochemically stressful conditions, such as those found in saline bays, alkaline lakes and hydrothermal or cold seep vents. Here we report one of the oldest occurrences of a vent camp coupled with cold seepage of methane in the geologic record, associated with well-preserved microbialites and elephant skin structures. During the seep activity, oxygen depletion and high salinity conditions are prohibitive for complex animal life, clearing the way to microbial colonies to flourish. Due to the co-occurrence of high adaptability and low competitiveness of microbial forms, they became highly specialized in stressful conditions. We argue that the sporadic microbial mat upturns in Earth's history are not restricted to geological periods, following massive death of metazoan species; they also may occur in response to punctual paleoenvironmental conditions that enable microbial colonies to growth. Indeed, the Phanerozoic geological record is punctuated of these examples, in a kind of hide-and-seek game of Precambrian times.
Keywords: Methane cold seeps; microbial mats; ecospace; Permian; Irati Formation